The Global Effects of Fund-Supported Adjustment Programs - Goldstein, Morris (Washington, D.C. : International Monetary Fund, 1986)
This is the second of a group of papers dealing with various aspects of Fund-supported adjustment Programs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet